Development of four-tier multiple-choice diagnostic instrument to identify middle school students' misconceptions about biology material - Sari, Tasya Novian Indah; Pantiwati, Yuni; Fauzi, Ahmad (Biosfer: Jurnal Pendidikan Biologi, 2024)
Misconceptions are a condition where students have a mismatch between personal and scientific concepts that influence the learning process. Efforts to identify misconceptions using the Four-Tier Multiple Choice (4TMC) Diagnostic instrument. The aim of the research was to develop the 4TMC diagnostic instrument to identify misconceptions and types of misconceptions of Class VII students regarding the classification of living things. Type of research Research & Development. The research was carried out October 2021-March 2022 at one of the State Middle Schools in Magetan Regency, Indonesia. Subject 4TMC students 197 Class VII students. Data collection techniques using tests and non-tests. Non-test instruments in the research include teacher interview sheets and expert validation sheets. Meanwhile, the test instruments include the two-tier open ended and 4TMC tests. The research results showed that the assessment by experts and teachers obtained a feasible instrument. Testing the validity of the question items obtained 43 valid questions with a reliability degree of 0.848. The questions consist of 10 difficult questions and 33 medium questions. Furthermore, 6 different power questions were poor, 13 different power questions were sufficient and 24 different power questions were very good. Apart from that, the results of the misconception test showed that 47% of students had moderate misconceptions, 28% understood the concept, 17% did not understand the concept and 7% made errors. The types of misconceptions that occur among students include three forms, namely classificational misconceptions 44%, correlational misconceptions 33% and theoretical misconceptions 13%. The results of instrument development can be used again to identify misconceptions and types by teachers or future researchers.